Outline of tourism development in the Łódź region - Włodarczyk, Bogdan (Acta Geographica Lodziensia, 2019)
The article presents the most important aspects of tourism development in the Łódź region against the background of the most important periods in the development of this phenomenon in Poland. Particular attention has been focused on the last one hundred years, during which the Łódź Voivodeship has existed within the administrative division of the country. The development of the phenomenon was also periodised, and the distinguished periods were characterised, indicating their characteristic features.